Applying the power rule of exponents, we know that (a^m)(a^n) equals a^(m+n).
Therefore, we can simplify the expression as follows:
(12 • 12 • 12) • (12 • 12 • 12) = 12^(1+1+1) • 12^(1+1+1)
Simplifying further, we have:
12^(1+1+1) • 12^(1+1+1) = 12^3 • 12^3
Now, to find the final answer, we apply the power rule again:
12^3 • 12^3 = 12^(3+3) = 12^6
So, the simplified equivalent expression is 12^6.
Use the Power Rule of Exponents to create a simplified equivalent expression of (12 • 12 • 12) • (12 • 12 • 12).
1 answer